Driving Sustainable Business Performance through Green HRM: Examining the Mediating Roles of Green Technology Innovation and Green Organizational Culture - Rahman, Md Abidur; Saba, Nazifa Anbar (Manunggal Halim Jaya, 2025)
Amid rising environmental challenges and competitive dynamics, organizations are progressively adopting sustainable human resource practices to secure a strategic edge. This study investigates the contribution of Green Human Resource Management (GHRM) to sustainable business performance (SBP), emphasizing the mediating roles of Green Technology Innovation (GTI) and Green Organizational Culture (GOC). Grounded in the Resource-Based View (RBV) and Ability-Motivation-Opportunity (AMO) theory, the research employs a quantitative approach, drawing data from multinational and local corporate organizations across the financial, telecommunications, and FMCG sectors in Dhaka and Chattogram, Bangladesh. Structural equation modeling (SEM) was employed to examine the proposed relationships. The results indicate that Green HRM positively influences business performance both directly and indirectly through GTI and GOC, highlighting their strategic importance as intangible assets and capability-enhancing mechanisms. This study advances theoretical understanding by integrating RBV and AMO perspectives and offers practical insights for managers seeking to embed sustainability into core HR and innovation strategies.